Den norske lokalpressen med Glamdalen som eksempel – fortiden og natiden - Przepióra, Agnieszka (Folia Scandinavica Posnaniensia, 2007)
Local newspapers are the spine of the Norwegian system of the press. About 200 yarious papers reach readers throughout the country and an average reader devotes over 30 minutes to reading daihes. It seems that even the expansion of the internet, as a source of information, is not able to weaken the remarkable position of local newspapers in Norway.